Protestants : the faith that made the modern world - Ryrie, Alec (New York, Viking, 2017)
On the 500th anniversary of Luther's rebellion, this spectacular global history traces the revolutionary faith that shaped the modern world. Five hundred years ago Protestant Christianity began with one stubborn monk. Today, it includes a billion people across the globe. The upheaval Martin Luther triggered inspired one of the most creative and destructive movements in human history. Protestants is the story of the men and women who made and remade this quarrelsome faith. Fired by life-changing encounters with their God, they set out for every corner of the world, demanded alarming new freedoms and experimented in new systems of government. Inspired by their newly accessible Bibles, they transformed their inner lives, a transformation that spilled over into social upheavals and political revolutions. In the process, they have played decisive roles on both sides of the great ideological battles of modern times. Protestants have been both for and against liberalism, imperialism, slavery, Nazism, communism, apartheid and women's rights. Yet beneath it all is a shared passion for God, a vital belief in the principle of self-determination and a readiness to fight for their beliefs. As this ever-changing faith puts down deep roots across contemporary China, Africa, and Latin America, Alec Ryrie's dazzling history explores how its restless energy made and is still making the modern world. - Publisher
Five hundred years ago, an obscure monk challenged the authority of the pope with a radical new vision of what Christianity could be. The revolution he unwittingly set in motion has toppled governments, upended social norms, and transformed millions of people's understanding of their relationship with God. In this dazzling global history charting five centuries of innovation and change, Alec Ryrie makes the case that the world we live in was indelibly shaped by Protestants. Protestants introduces us to the men and women who defined this quarrelsome faith. Some turned to their newly accessible Bibles to justify bold acts of political opposition, others to support a new understanding of how they should live. Protestants are conditioned to fight for their beliefs, and if you look at any of the great confrontations of the last five centuries, you will find them defining the debate on both sides: for and against monarchy, colonialism, slavery, fascism, communism, temperance, and war. Protestants are people who love God and take on the world. They have set out for all four corners of the globe, embarking on courageous journeys into the unknown to establish new communities and experiment with radical new systems of government-- like the Puritans, Quakers, and Methodists who made their way to our shores. Protestants created America and defined its special brand of entrepreneurial diligence. And today they are making new converts in China, Korea, Africa, and Latin America. This magisterial book by a brilliant scholars of the Reformation makes the case that whether or not you are yourself a Protestant, you live in a world-- and are guided by principles and ideas-- shaped by Protestants
Five hundred years ago, an obscure monk challenged the authority of the pope with a radical new vision of what Christianity could be. The revolution he unwittingly set in motion has toppled governments, upended social norms, and transformed millions of people's understanding of their relationship with God. Ryrie makes the case that the world we live in was indelibly shaped by Protestants, and introduces us to the men and women who defined this quarrelsome faith
Central Europe in the mid-sixteenth century -- Introduction -- Part I. The Reformation Age. Luther and the fanatics -- Protectors and tyrants -- The failure of Calvinism -- Heretics, martyrs, and witches -- The British maelstrom -- From the waters of Babylon to a city on a hill -- Part II. The modern age. Enthusiasm and its enemies -- Slaves to Christ -- Protestantism's wild west -- The ordeals of liberalism -- Two kingdoms in the Third Reich -- Religious left and religious right -- Part III. The global age. Redeeming South Africa -- Korea in adversity and prosperity -- Chinese Protestantism's long march -- Pentecostalism : an old flame -- Epilogue : the Protestant future
Includes bibliographical references (pages 475-495) and index
Keywords: Protestantism -- History; Church history; History